Active Materials for Medical Applications - Cimpoesu, Nicanor; Cimpoesu, Ramona (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue was proposed by and for engineers, physicists, medical doctors, researchers and scientists. We intend to analyze and discuss different topics on special materials for medical applications. There is great potential in the application of active or smart materials (metallic, polymer or ceramic) for the progression of applications in the medical domain of MEMS, actuators, sensors or functional systems. Active or "smart" materials have the ability to respond to different physical or chemical stimuli in a specific, repeatable mode. The actual activity in the domain, however, presents problems connected to obtaining, processing, characterizing, modeling and simulating or prototyping technologies. This Special Issue focuses on the most recent advances in obtaining and thermal and mechanical processing active materials used in the medical field with enhanced performances.